Table of Contents and Introduction - Jim Hoy; Larry Patton; Marty White (Symphony in the Flint Hills, 2015)
This journal includes the table of contents of the 2015 Symphony in the Flint Hills, art work by Lisa Grossman, introduction and the names of editors.
Keywords: table of contents; introduction; editors; art